INTEGRATED REASSESSMENT OF HYDROCARBON POTENTIAL IN THE ABSHERON-BANK AND DARWIN BANK FIELDS, OF THE ABSHERON-PREBALKHAN STRUCTURAL THRESHOLD - ABDULLA-ZADA, Murad; ZAHIDOVA, Tamella; SHAHBAZOV, Rufat (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The South Caspian Basin represents an exceptional geodynamic province distinguished by its extraordinary sedimentary accumulation and active petroleum systems, positioning it among the foremost hydrocarbon-bearing regions globally. Encircled by collisional orogenic belts, the basin has accommodated over 25 kilometers of sedimentary infill, more than 10 kilometers of which have been rapidly deposited within the last six million years. This accelerated subsidence and burial, under anomalously low geothermal gradients, has facilitated ongoing hydrocarbon generation at depths exceeding 8–12 kilometers. Regionally extensive anticlinal structures, interpreted as buckle folds developed above a basal detachment surface, have been delineated through the interpretation of regional-scale 2D seismic datasets. The convergence of an actively generating petroleum system, vast undrilled structural closures, and a regulatory framework conducive to foreign investment has elevated the basin’s profile within the global energy sector. Within this tectonically complex setting, the Absheron–Prebalkhan structural zone constitutes a principal hydrocarbon province, encompassing several strategically significant fields, notably the Absheron-Bank and Darwin Bank fields. This investigation offers a rigorous, data-integrated evaluation of their hydrocarbon prospectivity, synthesizing multi-decadal exploration, production records, and subsurface geoscientific data. The Absheron-Bank field, discovered in 1951 some 25 km north of Pirallahi Island in shallow Caspian waters, and the Darwin Bank field, delineated in 1950 and sharing structural continuity with neighboring anticlinal trends, serve as focal points of this assessment. Methods. Geological and geophysical analyses were conducted to evaluate reservoir properties, including stratigraphic correlations, reservoir pressures, and production performance. Core lithology and seismic data were integrated with petrophysical parameters – such as porosity, permeability, and fluid saturations – to characterize productive horizons (e.g., Kirmaki and Kala suites). Results. The results underscore substantial hydrocarbon accumulations within Lower Pliocene strata of the Productive Series. The Absheron-Bank field possesses estimated initial reserves (B+C1+C2 categories) of 6.3 million tonnes of crude oil and over 2.5 billion cubic meters of both dissolved and free gas. As of January 2022, 74 wells have been drilled, yielding 495.8 thousand tonnes of oil and approximately 1.2 billion cubic meters of gas – representing a 39.4 % recovery of extractable oil reserves. Conversely, the Darwin Bank field, developed through 776 wells, has produced approximately 17.9 million tonnes of oil and 1.4 billion cubic meters of dissolved gas, with nearly 80 % of extractable reserves already recovered. Current development efforts are situated in the terminal phase of the field’s productive lifecycle, where diminishing well productivity and infrastructure obsolescence pose persistent operational challenges. Conclusions. This study advocates for the continued implementation of reservoir pressure maintenance strategies, enhanced oil recovery (EOR) techniques, and the optimization of water injection regimes to prolong field productivity. Furthermore, it highlights the necessity of sustained geological, petrophysical, and hydrodynamic monitoring to inform adaptive field management strategies – particularly within mature, offshore domains of the South Caspian petroleum province.